THE PORTRAYALS OF "JOURNEY" IN JOHN GREEN'S TWO NOVELS LOOKING FOR ALASKA AND PAPER TOWNS - Utami, Rendila Restu (2015)
The study compares and contrasts two of John Green's two novels entitled Looking for Alaska and Paper Towns. The research in this study is conducted to understand how the similarities and differences in the portrayals of journey inside Green's two novels construct the main characters' identity. This research is qualitative in nature with a structuralism approach using Narratology. This research is carried out within the framework of Narratology employing Barthes' Hermeneutic Code and Proairetic Code to see the implicit features and elements behind the plot of the two novels. The findings of this research reveal that the similarities and differences in the portrayals of journey construct the main characters' identity by showing how the journey taken contributed to the changing of their identity. The role of the portrayal of journey is to show the young adult readers that there are many ways to cope with the change in their lives and that the journey, metaphorical or literal, still contributed to the changing of one's identity. Studi ini membandingkan perbedaan dan persamaan kedua buku John Green yang berjudul Looking for Alaska dan Paper Towns. Penenelitian ini dilaksanakan untuk memahami bagaimana persamaan dan perbedaan dalam penggambaran perjalanan dalan kedua novel karya Green membangun konsep identitas karacter utamanya. Penelitian ini bersifat kualitatif dengan pendekatan strukturalisme menggunakan Naratologi. Penelitian ini dilaksanakan dalam kerangka Naratologi menggunakan Hermeneutic Code dan Proairetic Code milik Barthes untuk melihat unsur - unsur implisit di balik alur cerita kedua buku tersebut. Penemuan penelitian ini memperlihatkan bahwa persamaan dan perbedaan dalam penggambaran perjalanan membangun identitas karakter utama dengan memperlihatkan bagaimana perjalanan yang telah ditempuh berkontribusi dalam perubahan identitas karakter utamanya. Peran penggambaran perjalanan adalah untuk memperlihatkan kepada para pembaca remaja bahwa ada banyak cara untuk menghadapi perubahan dalam kehidupan mereka dan perjalanan itu, baik metaforikal atau literal, tetap berkontribusi dalam perubahan identitas seseorang.